Infectious diseases in children and adolescents in the Republic of Korea; Past & recent status - Jong-Hyun Kim (Korean Journal of Pediatrics, 2011)
Compared to the past decades, in recent decades, environmental and hygienic conditions in the Republic of Korea have improved along with socioeconomic developments, and the incidence of most infectious diseases, especially vaccine-preventable diseases, has greatly decreased due to active immunization with the developed level of health care. However, the incidence of some diseases has been increasing, and new diseases have been emerging. To cope with such changes actively, the government put the "Law for Control and Prevention of Infectious Diseases" into effect; this law was entirely revised on December 30, 2010. In this report, I review the past and recent status of infectious diseases in the Republic of Korea, following the introduction of this law, on the basis of data in the "National Notifiable Disease Surveillance System", which had been accumulated between the years 1960 and 2010.